Analysis of Pharmacological Activities and Mechanisms of Essential Oil in Leaves of C. grandis ‘Tomentosa’ by GC-MS/MS and Network Pharmacology - You, Jie-Shu; He, Sheng-Cai; Chen, Liang; Guo, Zhen-Hui; Gao, Fei; Zhang, Min-Yue; Dan, Liu; Chen, Wei (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Citrus grandis ‘Tomentosa,’ a fruit epicarp of C. grandis ‘Tomentosa’ or C. grandis (L.) Osbeck is widely used in health food and medicine. Based on our survey results, there are also rich essential oils with bioactivities in leaves, but the chemical compounds in this part and relevant pharmacological activities have never been studied systematically. Therefore, this study was to preliminarily decipher the pharmacological activities and mechanisms of the essential oil in leaves of C. grandis ‘Tomentosa’ by an integrated network pharmacology approach. Methods: Essential oil compositions from leaves ofC. grandis ‘Tomentosa’ were identified using GC-MS/MS. And then, the targets of these oil compositions were predicted and screened from TCMSP, SwissTargetPrediction, STITCH and SEA databases. STRING database was used to construct the protein-protein interaction networks, and the eligible protein targets were input into WebGestalt 2019 to carry out GO enrichment and KEGG pathway enrichment analysis. Based on the potential targets, disease enrichment information was obtained by TTD databases. Cytoscape software was used to construct the component-target-disease network diagrams. Results: Finally, 61 essential oil chemical components were identified by GC-MS/MS, which correspond to 679 potential targets. Biological function analysis showed 12, 19, and 12 GO entries related to biological processes, cell components and molecular functions, respectively. 43 KEGG pathways were identified, of which the most significant categories were terpenoid backbone biosynthesis, TNF signaling pathway and leishmaniasis. The component-target-disease network diagram revealed that the essential oil compositions in leaves of C. grandis ‘Tomentosa’ could treat tumors, immune diseases, neurodegenerative diseases and respiratory diseases, which were highly related to CHRM1, PTGS2, CASP3, MAP2K1 and CDC25B. Conclusion: This study may provide new insight into C. grandis ‘Tomentosa’ or C. grandis (L.) Osbeck and may provide useful information for future utilization and development.
Keywords: component-target-disease